Polysemy in Translator's Footnotes in Sun Tzu's The Art of War - Stenfors, Susanna (My University, 2026)
This thesis examines how a translator can use footnotes to provide additional information to the reader in cases of polysemy. The aim of this research is to analyze how polysemy is mentioned, explained and discussed in translator’s footnotes in Jonathan Clements’ 2012 translation of Sun Tzu’s The Art of War. To effectively analyze these footnotes, different categorizations are used to examine what kind of footnotes are used to discuss polysemy. This thesis also considers how The Art of War and classical Chinese exhibit special characteristics that warrant the use of footnotes, as well as how footnotes act as an important tool for the understanding of the underlying linguistic and cultural elements in the source text. Footnotes are also compared to other paratexts and their unique features are discussed. This study concludes that footnotes provide a useful way of adding information regarding cases of polysemy without having to take up a considerable amount of space in the main text body.
Keywords: Translator's footnotes, polysemy, The Art of War